2021
DOI: 10.1016/j.tips.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for microRNA-targeting therapeutics for epilepsy

Abstract: Epilepsy is a common and serious neurological disorder characterised by recurrent spontaneous seizures. Frontline pharmacotherapy includes small-molecule antiseizure drugs that typically target ion channels and neurotransmitter systems, but these fail in 30% of patients and do not prevent either the development or progression of epilepsy. An emerging therapeutic target is microRNA (miRNA), small noncoding RNAs that negatively regulate sets of proteins. Their multitargeting action offers unique advantages for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 108 publications
0
45
0
Order By: Relevance
“…ASO mechanisms of action 41 can include steric blocking of mRNA translation, degradation of target mRNA or regulation of RNA splice events 42 . Different ASOs may also have different lengths and chemistries, which can affect their uptake, bioavailability and cellular effects 8 . Our methodology provides a platform which could be used to test all of these ASO mechanisms and properties in real human brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASO mechanisms of action 41 can include steric blocking of mRNA translation, degradation of target mRNA or regulation of RNA splice events 42 . Different ASOs may also have different lengths and chemistries, which can affect their uptake, bioavailability and cellular effects 8 . Our methodology provides a platform which could be used to test all of these ASO mechanisms and properties in real human brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…One leading preclinical solution to this problem targets the microRNA (miRNA) system [8][9][10][11] . MiRNAs are endogenous ~22nt noncoding RNAs which repress the translation of targeted mRNAs via complementary binding to targets regions in the 3' UTR 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the multi-targeting and multi-pathway actions of miRNAs, prediction and therapeutic function are not easy to approach. Several functional studies have shown the potential therapeutic targets of epilepsy on miRNA levels through administration of chemically engineered antisense oligonucleotides that target specific miRNAs called mimics or antagomirs, which are capable of reproducing or inhibiting specific miRNA function, respectively [ 58 ]. It emerged from data that prolonged seizures in rodents cause up-regulation of miR-134, and levels of miR-134 are also higher in the brain of patients with drug-resistant TLE.…”
Section: Impact On Diagnosis and Prognosismentioning
confidence: 99%
“…There have been more than 300 studies on miRNA and epilepsy, and over 100 different miRNAs are altered in experimental models and human samples. Of these, there are 10-20 miRNAs that appear consistently dysregulated and for which there is functional evidence for effects on seizures (44).…”
Section: Future Directionsmentioning
confidence: 99%